Interaction of a spherical particle with a neutrally buoyant immiscible droplet in salt solution. (23rd November 2017) - Gao, Ya; Mitra, Subhasish; Wanless, Erica J.; Moreno-Atanasio, Roberto; Evans, Geoffrey M.
Graphical abstract: Highlights: Interactions of small particles with a stationary immiscible droplet studied. Separation distance, particle trajectory and attachment time quantified. Both elastic and inelastic impact interactions noted depending on the particle size. Increased surface hydrophobicity enhances particle attachment to droplet interface. DEM model provided reasonable agreements to the experimental measurements. Abstract: The complex interactions of rigid spherical particles with interface (e.g., gas-liquid or liquid-liquid) underpin important industrial applications such as the separation of minerals using flotation method. The objective of the present work was to investigate this interaction process both experimentally and theoretically involving different size of particles (radius ∼ 100–200 μm) with varying surface wettability (contact angle ∼ 50–70°) and a stationary neutrally buoyant immiscible oil-water interface (aniline droplet in salt solution) utilizing high speed imaging technique. The results showed that the particle size significantly affects the collision mechanism wherein collision with particle rebound was noted for larger size particles and collision without particle rebound was noted for the smaller size particles. Increasing surface hydrophobicity of the particles was found to be a governing factor that strongly attaches the particle to interface with immersion depth as high as ∼50% of particle radius. Collision polar angle was also noted to be a critical parameter that governs the attachment process. When collision polar angle was increased from 15° to 55°, attachment time was noted to increase by ∼2.5 times indicating decreasing probability of attachment. A discrete element model (DEM) was also developed to predict the interaction outcomes with suitable modification of the governing forces. To account for the effect of interface deformation, a spatially dependent capillary force profile was utilised incorporating the effect of interface deformation. The contact force model was modified to produce the collision with/without rebound outcomes. Also, the short range hydrodynamic drag force model was modified using suitable correction factors to account for the resistance in the intervening film between the approaching particle and the interface. Experimentally determined parameters such as droplet-particle separation distance, particle trajectory and velocity were compared with the DEM model predictions and reasonably good agreements were obtained.